A new silver dressing, StopBac, used in the prevention of surgical site infections. Issue 1 (27th March 2021) - Oliverius, Martin; Drozd, Jan; Bratka, Petr; Whitley, Adam; Mohlenikova Duchonova, Beatrice; Gürlich, Robert
Abstract: Ideal dressings of surgical wounds should provide moist, semi‐permeable, and antiseptic environments for optimal wound healing. To maximise patient comfort, surgical dressings must be hypoallergenic, not restrict movement, and allow patients to manage their personal hygiene. From the aspect of health care personnel, dressings should enable visual monitoring of the wound without the need for removing them, thus reducing the number of dressing changes. The active antimicrobial effect of silver cations has been demonstrated by many studies. StopBac is a unique surgical dressing based on the sol‐gel process. Silver cations are bound in a colloidal solution in an organic‐inorganic hybrid organosilicate oligomer. This gel is deposited on a pad using spray atomisation. The result is a polymer nanolayer matrix with prolonged and controlled release of silver ions. This pad forms part of a waterproof hypoallergenic transparent adhesive bandage. The goal of this study was to prospectively evaluate the ability of StopBac to prevent surgical site infections (SSIs) in patients after abdominal surgery. The secondary goal was to compare costs and determine the properties of this new material. A total of 32 patients were included in the study. The patients were followed up until their surgical wounds healed completely. An SSI occurred only in one patient.